2018
DOI: 10.1007/s10886-018-1018-1
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Floral Scent Compounds from Night-Blooming Araceae Pollinated by Cyclocephaline Scarabs (Melolonthidae, Cyclocephalini)

Abstract: Nocturnal flowering plants often release strong scents to attract their pollinators. Among night active flower visitors are cyclocephaline scarab beetles, which have been demonstrated to respond to uncommon volatile organic compounds released in high amounts by their host plants. In Araceae, the molecular structure of several such compounds is yet to be unveiled. We investigated headspace floral scent samples of Philodendron squamiferum, Thaumatophyllum mello-baretoanum, and Xanthosoma hylaeae by a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 37 publications
1
28
0
1
Order By: Relevance
“…Floral scent is important in many nocturnal plant-pollinator mutualisms [75]. Floral volatile chemistry has been characterized for taxa pollinated by moths [76][77][78], beetles [38,79,80], nocturnal bees [63,67,81], and to a lesser extent smaller nocturnal and crepuscular pollinators, such as mosquitoes [82] and thrips [47,83]. Parallels can be drawn between floral scent profiles of plants associated with nocturnal pollinator taxa; for example, moth-pollinated flowers often emit a combination of acyclic terpene alcohols (e.g.…”
Section: Floral Scentmentioning
confidence: 99%
“…Floral scent is important in many nocturnal plant-pollinator mutualisms [75]. Floral volatile chemistry has been characterized for taxa pollinated by moths [76][77][78], beetles [38,79,80], nocturnal bees [63,67,81], and to a lesser extent smaller nocturnal and crepuscular pollinators, such as mosquitoes [82] and thrips [47,83]. Parallels can be drawn between floral scent profiles of plants associated with nocturnal pollinator taxa; for example, moth-pollinated flowers often emit a combination of acyclic terpene alcohols (e.g.…”
Section: Floral Scentmentioning
confidence: 99%
“…1). This high overall intraspecific variation in scent was unexpected given that within-species variation in scent is limited in other species pollinated by cyclocephaline beetles (e.g., Gottsberger et al 2012;2013;Maia et al 2013b;2019a).…”
Section: Discussionmentioning
confidence: 92%
“…Beside these two compounds, Milet-Pinheiro et al (2017) found another four compounds that contributed in one of their samples at least 2 % to the total scent discharge: butan-2-yl acetate, (Z)-jasmone, dihydro-β-ionone, and two unknown compounds (Milet-Pinheiro et al 2017). Based on retention index and mass spectral information given by these authors, and recently published papers on novel scents in cyclocephaline pollinated plants (Maia et al 2019a;b) and in floral chemistry of Cyclanthaceae (Teichert et al 2018), these unknown compounds are isojasmol and dehydrojasmone. None of these compounds were detected in our samples (Tab.…”
Section: Discussionmentioning
confidence: 95%
“…The scents are used for communicating between plants and the other pollinators (Knudsen et al, 2006). Some night emitting compounds are attractive for pollinators such as moths (Morinaga et al, 2009;Dotterl et al, 2012), beetles (Maia et al, 2018).…”
Section: Discussionmentioning
confidence: 99%